2006
DOI: 10.1038/sj.emboj.7600975
|View full text |Cite
|
Sign up to set email alerts
|

Subtelomeric proteins negatively regulate telomere elongation in budding yeast

Abstract: The Tbf1 and Reb1 proteins are present in yeast subtelomeric regions. We establish in this work that they inhibit telomerase-dependent lengthening of telomere. For example, tethering the N-terminal domain of Tbf1 and Reb1 in a subtelomeric region shortens that telomere proportionally to the number of domains bound. We further identified a 90 amino-acid long sequence within the N-terminal domain of Tbf1 that is necessary but not sufficient for its length regulation properties. The role of the subtelomeric facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
73
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(83 citation statements)
references
References 68 publications
7
73
0
Order By: Relevance
“…Indeed, even telomeres composed entirely of vertebrate-type repeats are kept stable during mitotic growth (18,20,21). Remarkably, on these telomeres, the hallmark telomere binding protein Rap1p appears to be replaced with Tbf1p, and there is some evidence to show that this latter protein can maintain a telomere length regulatory mechanism (19,20). However, it remained unclear how this mechanism could ensure telomere capping and stability in this situation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, even telomeres composed entirely of vertebrate-type repeats are kept stable during mitotic growth (18,20,21). Remarkably, on these telomeres, the hallmark telomere binding protein Rap1p appears to be replaced with Tbf1p, and there is some evidence to show that this latter protein can maintain a telomere length regulatory mechanism (19,20). However, it remained unclear how this mechanism could ensure telomere capping and stability in this situation.…”
Section: Discussionmentioning
confidence: 99%
“…It remains unclear whether in the situation of ScVSc telomeres, the vertebrate-type repeats, via the binding of Tbf1p, do actively contribute to overall telomere length regulation. Tbf1p has been shown to be able to contribute to telomere length regulation (19) and to promote telomere elongation of short telomeres, at least in the absence of Tel1p (42). However, it is also possible that the ϳ75-to 145-bp vertebrate repeats are too short to separate the proximal repeats from the distal repeat tracts to allow the establishment of a new and distally located independent telomere (43).…”
Section: Discussionmentioning
confidence: 99%
“…For instance in S. cerevisiae, a function-unknown protein, Cue2 protein (accession number is NP_012833), has the Smr domain in its C-terminal region. A genome-wide study (51) has shown that Cue2 protein interacts with a subtelomeric protein, Tbf1, which negatively regulates telomerase-dependent elongation of the telomere (52). Although the mechanism underlying this regulation has been unknown, the branched-structure preference of the Smr endonuclease domain may be a clue for understanding it, because the telomere contains the branched DNA structures (53).…”
Section: Discussionmentioning
confidence: 99%
“…In budding yeast, deregulation of telomere size, stability and function is observed in rap1 mutants (Kyrion et al, 1993) and Rap1-Sir4 interactions play an important role in initiating the assembly of heterochromatin (Luo et al, 2002). Similarly, subtelomere proteins have been shown to negatively regulate telomere elongation (Berthiau et al, 2006), and SIR3 and SIR4 are required for the integrity of telomeres in budding yeast (Palladino et al, 1993).…”
Section: Discussionmentioning
confidence: 99%